Інформаційні теорії та можливі математичні описи економічних і суспільних систем, заснованих на фізичних явищах - Gaeta, M.; Iovane, G.; Makarenko, A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Recent approaches in informatics to model large complex systems are considered following the ideas from real phenomena explained by physical tools. The econophysics and sociophysics are considered. In particular, Master Equation approach and Markov chains approaches are discussed. Also the partial differential equations as the tool for modeling economical and social systems are represented. New approaches for modeling systems with memory and with accounting internal properties of system elements are considered and some new research problems are proposed.